(untitled) (Global Journal of Science Frontier Research, 2018)
Twenty-first century Theoretical Physics in undergoing a major ’Paradigmatic Shift’ due to the discovery of the ’Computational Unified Field Theory’ (CUFT) – from the current ’Material-Causal’ Paradigm underlying both ’Relativity Theory’ (RT) and ’Quantum Mechanics’ (QM) towards the CUFT’s new ’ACausal Computation’ Paradigm; As shown previously, this ’Paradigmatic Shift’ is warranted based on Kuhn’s (1962) well-known rigorous scientific criteria for the acceptance of a ’Paradigmatic Shift’ in Science, which includes: a) The existence of a basic "theoretical inconsistency" between the "pillars" of a given scientific discipline –i.e., the basic theoretical inconsistency that exists between RT